Athens from 1920 to 1940 : a true and just account of how history was enveloped by a modern city and the place became an event - Karidis, Dimitris N., (Archaeopress, 2016)
During the short interwar period of the early 20th century, Athens entered into a process of meteoric urban transformation which gave her a unique place among European capital cities of the time. This work examines this topic.